2019
DOI: 10.3389/fonc.2019.01432
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Somatic Allele Frequency in Combination With Blood-Based Tumor Mutational Burden to Predict the Efficacy of Atezolizumab in Advanced Non-small Cell Lung Cancer: A Pooled Analysis of the Randomized POPLAR and OAK Studies

Abstract: high bTMB or low MSAF (HR = 0.57 [95% CI, 0.47-0.69], P < 0.001; interaction test P < 0.001). Consistent findings were obtained for progression-free survival data. Conclusions: MSAF alone or in combination with bTMB can effectively distinguish patients with or without survival benefit from atezolizumab compared with docetaxel. MSAF and the combined bTMB-MSAF classification may become practical predictive markers for atezolizumab in advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 29 publications
1
27
0
1
Order By: Relevance
“…Many studies support the viewpoint that bTMB can be used as a biomarker to predict clinical efficacy in anti-PD-1/PD-L1 immunotherapy. Patients with high bTMB have a better ORR and PFS than patients with low bTMB ( 1 , 40 ). However, a retrospective analysis of the POPLAR and OAK studies found that bTMB may not effectively distinguish the benefit in OS of patients receiving immunotherapy at second-line or higher ( 1 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies support the viewpoint that bTMB can be used as a biomarker to predict clinical efficacy in anti-PD-1/PD-L1 immunotherapy. Patients with high bTMB have a better ORR and PFS than patients with low bTMB ( 1 , 40 ). However, a retrospective analysis of the POPLAR and OAK studies found that bTMB may not effectively distinguish the benefit in OS of patients receiving immunotherapy at second-line or higher ( 1 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the tissue sample, the tissue TMB (tTMB) is recognized as an accurate molecule as an approximation of tumor load, and the blood TMB (bTMB) could be a substitute for tTMB if necessary ( 65 ). Compared to tTMB, bTMB has easier access and less affected by biopsy.…”
Section: Tumor Mutational Burden As a Biomarkermentioning
confidence: 99%
“…Compared to tTMB, bTMB has easier access and less affected by biopsy. Analyzing the POPLAR trial (NCT01903993) and the OAK trial (NCT02008227), a positive-associated correlation between tTMB and bTMB is observed ( 65 ). More importantly, the accuracy of TMB detection, neither tTMB nor bTMB, requires to be further improved and harmonized as well.…”
Section: Tumor Mutational Burden As a Biomarkermentioning
confidence: 99%
“…A high MSAF is the prerequisite to precise detection of variants and a low MSAF has been shown to greatly contribute to the discordance between bTMB and tTMB [1,9]. Chen et al surprisingly found that NSCLC patients with both low bTMB and low MSAF could derive survival benefits from ICI over chemotherapy [10], in accordance with another study showing both low and high bTMB were associated with better OS than medium bTMB [11]. These results suggested that a proportion of patients might be wrongly classified into low-bTMB group due to a low MSAF value.…”
Section: Current Advancesmentioning
confidence: 99%